Transgenic overexpression of furin increases epileptic susceptibility. Issue 11 (November 2018) - Yang, Yi; He, Miaoqing; Tian, Xin; Guo, Yi; Liu, Feng; Li, Yun; Zhang, Haiqing; Lu, Xi; Xu, Demei; Zhou, Ruijiao; Ma, Yuanlin; Wang, Wei; et al.
Abstract The proprotein convertase Furin plays crucial roles in the pathology of many diseases. However, the specific role of furin in epilepsy remains unclear. In our study, furin protein was increased in the temporal neocortex of epileptic patients and in the hippocampus and cortex of epileptic mice. The furin transgenic (TG) mice showed increased susceptibility to epilepsy and heightened epileptic activity compared with wild-type (WT) mice. Conversely, lentivirus-mediated knockdown of furin restrained epileptic activity. Using whole-cell patch clamp, furin knockdown and overexpression influenced neuronal inhibitory by regulating postsynaptic gamma-aminobutyric acid A receptor (GABAA R)-mediated synaptic transmission. Importantly, furin influenced the expression of GABAA R β2/3 membrane and total protein in epileptic mice by changing transcription level of GABAA R β2/3, not the protein degradation. These results reveal that furin may regulate GABAA R-mediated inhibitory synaptic transmission by altering the transcription of GABAA R β2/3 subunits in epilepsy; this finding could provide new insight into epilepsy prevention and treatment.